Geguritan Mantri Sanak Lima Analisis Struktur Dan Nilai - Noviyanti Wardani, Ni Putu; Duana Sutika, I Nyoman; Rai Putra, Ida Bagus (Humanis; Vol 17 No 3 (2016), 2016)
Research on Geguritan Relatives of Mantri Lima aims to analyze the structure and nilai.Teori used in this study is the structural theory and the value of Teeuw, Luxemburg, and Wellek & Warren.Metode used include methods refer, qualitative methods, and methods informal.Teknik recording techniques used are assisted with translation techniques. The result of this research is to build a structure terungkapanya Relatives of Mantri Geguritan Lima both narrative structure and values ??contained therein. Narrative structure which includes incident, plot, setting, character and characterization, theme and mandate. Values ??contained in the Lima Relatives of Mantri Geguritan ie religious values, ethics, values ??loyalty, and the value of leadership. The theme of GMSL is togetherness, united, together, shoulder to shoulder, to build strength so that the successes achieved. Then the mandate in GMSL that as children must always obey the commands and advice given by the parents kita.Dibalik all the advice given must be a reason or cause, where it's all for the good of their children. Therefore let us not forgot the advice of our parents.